Isolation of human cytomegalovirus intranuclear capsids, characterization of their protein constituents, and demonstration that the B-capsid assembly protein is also abundant in noninfectious enveloped particles. - Irmiere, A (1985)
Two types of intranuclear capsids have been recovered from human cytomegalovirus (HCMV, strain AD169)-infected cells. By analogy with strain Colburn (simian CMV) particles, these have been designated as A- and B-capsids. Both types of capsids are composed of proteins with molecular weights of 153,000 (major capsid protein), 34,000 (minor capsid protein), 28,000, and 11,000 (smallest capsid protein). In addition to these species, B-capsids contain a 36,000-molecular-weight (36K) protein which has been designated as the HCMV "assembly protein," based on its similarities to counterparts in strain Colburn CMV (i.e., 37K protein) and herpes simplex virus (i.e., VP22a/p40/NC-3/ICP35e). Peptide comparisons established that the assembly protein of HCMV B-capsids and the 36K protein that distinguishes HCMV noninfectious enveloped particles from virions are the same, providing direct evidence that noninfectious enveloped particles are enveloped B-capsids.